Emancypacyjne czy instrumentalne – (re)konstrukcja kształcenia kompetencyjnego - Przybylska, Irena (Studia Edukacyjne, 2020)
The main aim of the text is to (re)construct competence education in the context of three orientations: technical, humanistic and critical. Competences are discussed as practical and epistemological categories. It is a complex term, which carries the risk of simplification of meaning and structure. In the instrumental (technical) perspective, competences are reduced to skills and education to behavioural teaching. Due to reconstruction of competences in the context of humanistic orientation, concentration on a person and the process of “becoming” shifted the focus from “effects” of educational influence to the process of development and learning itself. Following this approach, education is not necessarily a process of acquiring competences, but rather a process of their exploration, creation and extension. Individuals will not be able to develop competences if they do not participate in the process of learning. The source of third, critical orientation, lies in progressivism, cognitive psychology, critical thought, and functional epistemology. Reconstruction is based, among others, on thoughts of Jurgen Habermas, Lawrence Kohlberg and Maria Czerepaniak–Walczak. In this orientation, competences have to be understood in a dynamic way. They are rather an open, cognitive structure which is subjected to constant reorganisation than a set of skills, knowledge or attitudes. The development of competences can be identified with progress to higher levels of development, enabling broadening of both cognitive and individual competences. The author intends to advocate for critical and emancipatory dimensions of competence-based learning as a way to overcome discrepancies between either only practical or theoretical education. The text yields arguments for education which increases reflectivity, strengthens personal identity as the core of competence.